Need for objective and reproducible criteria in histopathological assessment of total mesorectal excision specimens: lessons from a national improvement project. (November 2013) - Demetter, P.; Vandendael, T.; Sempoux, C.; Ectors, N.; Cuvelier, C. A.; Nagy, N.; Hoorens, A.; Jouret‐Mourin, A.; ,
Abstract Aim Data on quality control of the pathologic evaluation of total mesorectal excision (TME) specimens are scarce. We aimed to assess differences between evaluation by local pathologists participating in PROject on CAncer of the REctum (PROCARE; a Belgian improvement project on rectal cancer) and by a review panel of experts. Method Based on photographic material and histopathology slides, a Review Committee of gastrointestinal expert pathologists re‐evaluated the mesorectal plane, the tumour differentiation grade, the (y)pT stage and the tumour regression grade in 444 patients previously routinely assessed by local pathologists. Results The surgical plane was reported in 89% of patients and the circumferential resection margin in 88% of patients by the local pathologist. The median number of lymph nodes harvested in patients undergoing neoadjuvant radiochemotherapy was 11 and 14 in the other patients. The Review Committee downgraded the surgical plane from (intra)mesorectal to intramuscular in 17% of patients, and upgraded it from intramuscular to (intra)mesorectal in 27%. Tumour differentiation grade, T stage and tumour regression grade differed between local pathologists and the Review Committee in 15%, 10% and 38%, respectively, of patients. T stage was upgraded, mainly from T2 to T3, in 8% of patients. Tumour regression was judged by the Review Committee to be less advanced in 15% of patients. Conclusion Acknowledging some shortcomings, this study gives a realistic view of clinical practice. There are differences in interpretation with regard to both macroscopic and microscopic analysis of TME specimens. These findings indicate a need for more objective and reproducible criteria in histopathology. Being aware of this is a first step for improvement.